2018
DOI: 10.1016/j.mtcomm.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on low-velocity impact response of wood skinned sandwich composites with different core configurations

Abstract: In this paper, an experimental investigation on the low-velocity impact response of wood skinned hybrid sandwich composites was presented. Several alternative design configurations were developed by using rubber-cork and E-glass composite layers between the foam core and wood skin in order to improve the impact performance of conventional sandwich composites. Low-velocity impact (LVI) testing was performed using a drop weight test machine at different impact energies and destructive cross-sectioning was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 37 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…In a very interesting study, the beneficial effect of wood used as a shield against hypervelocity impacts was also demonstrated by Wen et al [29]. Sandwiches with classical foam cores but with intermediate layers made of ash wood or rubber cork have been analyzed under low-velocity impact and the benefit of the additional layers was demonstrated by Demircioğlu et al [30]. The same authors also studied the compression after impact response of this kind of sandwich [31] and this is the only reference found on this subject to date.…”
Section: Introductionmentioning
confidence: 89%
“…In a very interesting study, the beneficial effect of wood used as a shield against hypervelocity impacts was also demonstrated by Wen et al [29]. Sandwiches with classical foam cores but with intermediate layers made of ash wood or rubber cork have been analyzed under low-velocity impact and the benefit of the additional layers was demonstrated by Demircioğlu et al [30]. The same authors also studied the compression after impact response of this kind of sandwich [31] and this is the only reference found on this subject to date.…”
Section: Introductionmentioning
confidence: 89%
“…This renewal of interest is also shared by the academic world and recent studies demonstrate the interest of wood alone or in combination with natural fibres or modern materials such as glass, Kevlar, carbon or even aluminium, in particular in sandwich form [10][11][12][13][14][15][16]. An increasing number of recent academic studies have also shown that wood has very good mechanical characteristics at low speed-low energy impact [17][18][19][20][21][22][23] and in compression after impact, with behaviour that is sometimes surprising compared to that of composites.…”
Section: Introductionmentioning
confidence: 94%
“…The structure and material of the core influence the strength and stiffness of sandwich panels. Core structures include foam [ 1 , 2 , 3 , 4 ], corrugated [ 5 , 6 , 7 ], and honeycomb cores [ 8 , 9 , 10 ]. Core materials include metals [ 11 , 12 , 13 ], polymers [ 14 , 15 , 16 ], and composite materials [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%